Analysis of Determinants of Nurses' Perception of Hospital Occupational Health and Safety at Hospital X Batam City - Parisma, Wan Intan; Sari, Chinta Yolanda; Jayati, Trisna (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Nurses are the health workers with the largest presentations and play an important role in the provision of health services. Hospital Occupational Safety and Health is all activities to ensure and protect the safety and health of hospital human resources. Objective: The purpose of this study is to find out the perception of nurses about hospital occupational safety and health at Regional General Hospital X Batam City. Method: The research design is cross sectional. The research population is nurses who work at Regional General Hospital X Batam City with a sample of 73 people who were taken by the proportional sampling method. Data analysis was carried out using chi-square. Result and Discussion: The results of the analysis showed that there were 53.4% of respondents with a bad perception of Occupational Safety and Health, 71.2% of respondents with a new working period, 56.2% of respondents who had never participated in HOHS training, 90.4% of respondents who had good knowledge and 69.9% of respondents with undergraduate education. Conclusion: The results of the statistical test showed that there was a significant relationship between the length of service (p-value 0.007), HOHS training (p-value 0.000), knowledge (p-value 0.003) and education level (p-value 0.001) with the perception of nurses about hospital occupational safety and health at Regional General Hospital X hospital safety, knowledge and nurse education level.